Psychographic profiles and emotional intelligence of potential first class undergraduates in Universiti Utara Malaysia - Ishak, Noor Azniza (Universiti Utara Malaysia, 2012)
The success of the nation depends on the young generation who are equipped with emotional intelligence (EI) and have stable psychographics characteristics. The objectives of this study are to identify the EI levels and psychographic characteristics among the first class students in Malaysia public universities and to compare the levels of EI among demographic attributes.This research will also identify the relationships between dimensions of EI among first class students. This study uses a self report questionnaire as the instrument to collect data which consist of questions related to EI characteristics (self-awareness, self-regulation, motivation, empathy, and social skills) and psychographics attributes (achievement motivation, self-efficacy, time management, and leisure attitude).The population of this study consist of 424 students who are potential first class undergraduate students in UUM. This group consists of the students who obtained at least 3.50 of the CGPA within the duration of this study was conducted.This study reports the result of the descriptive profile of the respondents, presented the level of EI among university students in Malaysia.The results of the study indicate that 69.4% of respondents are in the moderate level in total, 6.5 % fall into the low level and only 24.1% fall into the high level of EI.